Installation of Neutron Monitors at the Jang Bogo Station in Antarctica - Jongil Jung; Suyeon Oh; Yu Yi; Paul Evenson; Roger Pyle; Geonhwa Jee; Jeong-Han Kim; Changsup Lee; Jongdae Sohn (Journal of Astronomy and Space Sciences, 2016)
In December 2015, we have installed neutron monitors at the Jang Bogo station in Antarctica. The Jang Bogo station is the second science station which is located at the coast (74° 37.4´S, 164° 13.7´E) of Terra Nova Bay in Northern Victoria Land of Antarctica. A neutron monitor is an instrument to detect neutrons from secondary cosmic rays collided by the atmosphere. The installation of neutron monitor at Jang Bogo station is a part of transferred mission for neutron monitor at McMurdo station of USA. Among 18 tubes of 18-NM64 neutron monitor, we have completed relocation of 6 tubes and the rest will be transferred in December 2017. Currently, comparison of data from the neutron monitors of both two stations is under way and there is a good agreement between the data. The neutron monitors at Jang Bogo station will be quite useful to study the space weather when the installation is completed.